The Influence of Work Motivation and Compensation On Employee Performance at PT. Honest Jaya Sakti Makassar - Putri Salsabila; Zainal Ruma; Abdi Akbar; Romansyah Sahabuddin; Burhanuddin (PT Maju Malaqbi Makkarana, 2023)
Abstract This study aims to (1) determine the effect of work motivation on employee performance, (2) determine the effect of compensation on employee performance, (3) determine the effect of work motivation and compensation jointly on employee performance at PT. Jujur Jaya Sakti Macassar. The data used in this study are primary and secondary data with a total sample of 61 respondents who are located as salespeople. This study used a quantitative approach and was analyzed using multiple linear regression analysis with the help of SPSS 25 data processing to prove the four hypotheses. The results of this study prove that the variable work motivation has a significant effect on employee performance by 0.005. The compensation variable has a significant effect on employee performance of 0.000. Based on the results of this study it is also known that the independent variables jointly or simultaneously have a significant effect on the dependent variable, namely the performance of employees at PT.Jujur Jaya Sakti Makassar. Therefore, if work motivation and compensation continue to be improved, then of course it will improve employee performance to be more optimal.